Guillain-Barré syndrome in Mexico: An updated review amid the coronavirus cisease 2019 ERA - Javier A. Galnares-Olalde; Juan C. López-Hernández; Miguel García-Grimshaw; Sergio I. Valdés-Ferrer; María E. Briseño-Godínez; Adib J. de-Sarachaga; Marco A. Alegría-Loyola; Anna Bazán-Rodriguez; Eunice Martínez-Jiménez; Edwin S. Vargas-Cañas (Revista de Investigación Clínica, 2022)
Guillain-Barré syndrome (GBS) is the most frequent cause of acute flaccid paralysis and if not diagnosed and treated timely, a significant cause of long-term disability. Incidence in Latin America ranges from 0.71 to 7.63 cases/100,000 person-years. Historically, GBS has been linked to infections (mainly gastrointestinal by Campylobacter jejuni) and vaccines (including those against severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2]); however, a trigger cannot be detected in most cases. Regarding SARS-CoV-2, epidemiological studies have found no association with its development. Acute motor axonal neuropathy is the most common electrophysiological variant in Mexico and Asian countries. Intravenous immunoglobulin or plasma exchanges are still the treatment cornerstones. Mortality in Mexico can be as high as 12%. Avances in understanding the drivers of nerve injury in GBS that may provide the basis for developing targeted therapies have been made during the past decade; despite them, accurate criteria for selecting patients requiring acute treatment, prognostic biomarkers, and novel therapies are still needed. The newly-developed vaccines against SARS-CoV-2 have raised concerns regarding the potential risk for developing GBS. In the midst of coronavirus disease 2019 and vaccination campaigns against SARS-CoV-2, this review discusses the epidemiology, clinical presentation, management, and outcomes of GBS in Mexico.